RESOLUSI KONFLIK RUMAH IBADAH (STUDI KASUS ATAS KERUSAKAN MASJID AL AMIN) - Arifinsyah Arifinsyah; Husna Sari Siregar; Rahmad Syahputra Nasution (UIN Sumatera Utara Medan, 2021)
AbstarckIn dealing with a conflict between two groups, it is necessary to respect each other and be willing to listen to each other's opinions. Such as the social disparity in the community in KenanganBaru Village, Percut Sei Tuan District, regarding the sense of intolerance between Muslims who are worshiping and customers of the taverns who make a fuss by singing while music as loud as possible, so that a sense of intolerance and lack of other people's opinions. To get complete information about the problems that occur in the Kelurahan, I use a type of qualitative research method, namely research that aims to get closer to the in-depth description of the perpetrators, parties, victims and also observe from one individual to another in certain settings that are studied from the point of view. comprehensive social and religious sciences. The methodology used in this study is a sociological approach, which is an approach that focuses on the interaction of religion and society. After the holding of mediation by the BKM, FKUB and traditional leaders to resolve the problems between the mosque and the taverns, they held a peace agreement dialogue to tolerate and respect the opinions of others, and as a result, the life of the people of KenanganBaru Village has reached the peak of peace and there is no more rioting. as well as the destruction of places of worship.Keyword : Conflict Resolution, Religion, Houses of Worship.